Tersilochinae of Western Amazonia (Hymenoptera: Ichneumonidae). Genus Stethantyx Townes, part 2 - Khalaim, Andrey I.; Sääksjärvi, Ilari E.; Bordera, Santiago (Zootaxa, 2015)
In this paper we describe four new species of Stethantyx Townes (Ichneumonidae: Tersilochinae) from Ecuador and Peru characterized by the fore wing with first and second abscissae of radius meeting at right angle: S. erwini Khalaim & Sääksjärvi, sp. nov., S. radiata Khalaim & Sääksjärvi, sp. nov., S. rufispa Khalaim & Bordera, sp. nov. and S. undulata Khalaim & Sääksjärvi, sp. nov. Second part of the key to species of Stethantyx occurring in Western Amazonia is given. Additionally, S. altamira Khalaim & Broad and S. aprica Khalaim & Broad are recorded from South America for the first time, and new data on distribution of S. alajuela Khalaim & Broad, S. amazonica Khalaim & Sääksjärvi, S. heredia Kha-laim & Broad, S. orellana Khalaim & Sääksjärvi, S. sinuata Khalaim & Sääksjärvi and S. trepida Khalaim & Sääksjärvi in South America are provided. Male of S. orellana is recorded for the first time.